The expression of SP263 in muscle invasive bladder carcinoma and its relationship with clinicopathological features - Yanfeng Bai; Xuesong Wu; Menghan Weng; Qingmei Han; Liming Xu; Chengdong Chang; Xiaodong Teng (Wolters Kluwer Medknow Publications, 2023)
Context: The expression of programmed cell death ligand1 (PDL1) is a research hotspot of immunotherapy. The treatment targeted for its expression has shown effectiveness in many tumors. Objective: The aim of the study was to determine PD-L1 expression in urothelial carcinoma (UC) and to compare the PD-L1 expression in muscle invasive bladder carcinoma (MIBC) and upper urinary tract urothelial carcinoma (UTUC). The predictive value of CD8+ tumor-infiltrating lymphocyte (TIL) density for the diagnosis of PD-L1 positivity and the association between CD8+ TIL density and prognosis in MIBC were also explored. Materials and Methods: Immunohistochemistry (IHC) staining for PD-L1 (SP263), CK5/6, CK20, CD44, and p53 was carried out using a 3D Histech digital scanner to scan and determine CD8+ TIL density. Results: 122 patients received radical cystectomy, and the overall PD-L1 positivity was 34.43% (42/122). PD-L1 positivity in whole sections was higher than in tissue micro-array (TMA) (all P < 0.05). If multiple lesions were detected simultaneously, the number of patients with positive results increased from 42 to 49. The areas under the curve (AUCs) of CD8+ TIL density for the diagnosis of PD-L1 positivity were 0.739, 0.713, and 0.826. Univariate cox regression analysis demonstrated that high CD8+ TIL density and CD8highPDL1+ were protective factors of overall survival (OS), and multivariate cox analyses showed that only CD8+ TIL density was an independent prognostic factor for OS. For UTUC, the overall PD-L1 expression was 40.0% (16/40). Conclusions: Our study results emphasize the importance of detecting PD-L1 expression in multiple tumor lesions from the same patient. In MIBC, CD8+ TIL density could be used as a prognostic marker for predicting the status of PD-L1 expression.